Correlated evolution of self and interspecific incompatibility across the range of a Texas wildflower. Issue 1 (11th July 2018) - Roda, Federico; Hopkins, Robin
Summary: Selection to prevent interspecific mating can cause an increase or a decrease in self‐pollination in sympatric populations. Characterizing the geographical variation in self and interspecific incompatibilities within a species can reveal if and how the evolution of self and interspecific mate choice are linked. We used controlled pollinations to characterize the variation in self and interspecific incompatibility across 29 populations of Phlox drummondii . We evaluated seed set from these pollinations and described the developmental timing of variation in pollen–pistil compatibility. There is extensive quantitative variation in self‐incompatibility and interspecific‐incompatibility with its close congener P. cuspidata . Phlox drummondii populations that co‐occur and hybridize with P. cuspidata have significantly higher interspecific incompatibility and self‐incompatibility than geographically isolated P. drummondii populations. The strength of self and interspecific incompatibility is significantly correlated among individuals and the strength of both incompatibilities is explained by the success of pollen adhesion to the stigma. The correlated strength of self and interspecific incompatibility across the range of P. drummondii and the concurrent developmental timing of the pollen–pistil interaction, suggests these incompatibilities have an overlapping molecular mechanism. The geographical distribution of variation in incompatibilities indicates that this mechanistic link between incompatibilities may affect the evolution of mate choice in plants.